PENGARUH MODAL KERJA BERSIH, ARUS KAS OPERASI DAN BEBAN BUNGA TERHADAP NILAI PERUSAHAAN - Haekal Amin; Juanda Juanda (Departemen Manajemen, 2021)
This study aims to determine the effect of net working capital, operating cash flow, and interest expense on company’s value in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 19 consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) from the 2014-2018 period. The analytical method used is multiple regression analysis with random effect models. Partially the results of the study show that net working capital has a negative and significant effect on company’s value, operating cashflow has positive and significant effect on company’s value, and interest expense has no effect on positive direction on company’s value on consumer goods industry companies in Indonesia. In this study, all independent variables were tested simultaneously on the dependent variable with the result that there was a significant effect between the independent variables and the dependent variable.